Civil law regulation of the right to life and right to health in the field of chemical safety of the Republic of Kazakhstan - Dautbayeva-Mukhtarova, E.; Askarova, A.O.; Suleymenova, S.Z. (Middle-East Journal of Scientific Research 14 (4), 502-507, 2013)
This paper is to study the civil regulation of private non-property rights in the field of chemical safety as one of the most problem sectors of technological security due to increasing number of technogeneous disasters. The author provides a gradual transition from the study of the essence of private non-property relations in the civil law of the Republic of Kazakhstan to the rights to human life and health, their civil protection, features of its implementation in conditions of the chemical threats. Author presents the chemical safety as the systems consisting of numerous different-level elements with multiple connections and considers it as an integral part of national security. In this regard, the author assumes the necessity of the special methods to protect the private non-property rights to life and health and derived property rights. The author demonstrates the conceptual approach to study and indicates the need for the development and adoption of the Concept of chemical safety by showing that the right to life and health in the field of chemical safety are ensured by a complex legal, organizational, financial, material and information measures stipulated to prevent and eliminate the real and potential security threats and mitigation of their consequences.
Keywords: Life, Health, Personal non-property rights and benefits, Right to life, Right to health, Civil law, Civil law regulation, Civil-law responsibility, Chemical safety